Conflict, citizenship and civil society - Baert, Patrick , 1961- (Routledge/European Sociological Association studies in European societies, 2010)
Offers students, researchers, academics, policy-makers, activists and interested non-specialists with an understanding of contemporary discussion, analysis and theorizing of issues pertaining to conflict, citizenship and civil society.